The Development of Supervision Instruments and Implementation of Islamic Education Supervision: Conceptual Review and Secondary Case Study Analysis - Mariani, Mariani; Mof, Yahya; Hermina, Dina (ISLAMIC PEDAGOGY: Journal of Islamic Education, 2024)
Improving the quality of learning in educational institutions requires professional supervision supported by valid and relevant instruments. Supervision in the context of Islamic education presents unique challenges, as it must accommodate religious and spiritual values. This study aims to provide a conceptual review of the development of supervision instruments and analyze case studies of their implementation in Islamic education by using a literature review approach. This study reviews various academic sources and analyzes secondary case studies from MTs Negeri 1 Lubuklinggau and MAN 1 Sigli. The results indicate that the development of supervision instruments involves several steps, including framework design, validation, and trial phases. Supervision implementation in both madrasahs was carried out through observation, interviews, and evaluations, followed by teacher training and competency improvement programs. Both individual and group supervision techniques were utilized to achieve educational goals. This study concludes that developing valid supervision instruments and systematic implementation of supervision can significantly enhance the quality of Islamic education.